The China Price: The All-China Federation of Trade Unions and the Repressed Question of International Labour Standards. Issue 2 (23rd February 2017) - Lambert, Rob; Webster, Edward
Abstract: The focus of this paper is the character and role of the All-China Federation of Trade Unions (ACFTU) in securing and sustaining a cheap labour regime within China. This labour regime is shaping the character of neoliberal regimes across the globe with dire consequences for societies everywhere. We argue that the international labour movement has the potential to create a movement against this regime, a movement defined by the international labour standards (ILS). The rise of the Southern Initiative on Globalisation and Trade Union Rights (SIGTUR) is a southern network grounded in ILS. However, in spite of SIGTUR's commitment to independent trade unions there is division within the movement as some support the ACFTU on ideological grounds. We conclude by arguing that support for democratic unions in China can best be achieved by linking local workplace struggles to ongoing pressure on the ACFTU to apply ILS.